Cloning ORF2 Membrane Protein of Koi Herpesvirus Lake Toba, Indonesian Isolate - MURWANTOKO MURWANTOKO (Bogor Agricultural University, Indonesia, 2009)
Koi herpesvirus (KHV) caused significant morbidity and mortality in koi and common carp. KHV which showed strong antigenic property implied that KHV virion or proteins may be used as antigen to raise antibody or vaccine to increase the resistance. The objectives of this research were to (i) clone KHV membrane protein ORF2, (ii) analysis on immunogenicity, and (iii) genetic tracing. Based on genbank data, one pair of primers was designed to amplify KHV ORF2. The KHV ORF2 can be amplified using infected fish DNA which originally from Toba Lake, Sumatera, Indonesia. The KHV ORF2 composed of 699 nucleotides encoded for 292 amino acids. BLAST analysis showed that KHV ORF2 had 100% homology with KHV-J and KHV0301 strains from Japan; 98 and 91% homology on nucleotides and amino acids respectively with both KHV-U strain from Unites State and KHV-I strain from Israel. KHV in Indonesia was most likely to have originated from Japan via spreading directly or not directly to China or Hongkong. Based on T- and B-cell epitopes prediction, membrane protein ORF2 was proposed has a potency to be used in development vaccine and immunodetection. Key words: genetic tracing, koi herpesvirus (KHV), membrane protein, ORF2